Persepsi Publik Terhadap Akuntansi Syariah Melalui Sentiment Analysis pada Brand24: Studi Kasus Pembiayaan Mikro Syariah - Febianti, Dini; Fadhilah, Lailatul; Salsabila, Savira; Kamal, Muhammad Rikzam (PROGRAM STUDI AKUNTANSI SYARIAH FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2025)
This study is motivated by the importance of understanding how public perceptions are formed regarding Islamic accounting, particularly in the context of Islamic microfinance, which plays a crucial role in promoting financial inclusion and economic empowerment of communities in Indonesia. The objective of this study is to identify and analyze patterns of public sentiment toward Islamic microfinance through a digital sentiment analysis approach using the Brand24 tool. The research employs a qualitative descriptive method within a constructivist paradigm, with data collected non-participatively through online monitoring across various social and non-social media platforms during the period from April 19 to May 19, 2025. A total of 9,546 mentions were detected, reaching an audience of 38 million people. The analysis results showed a dominance of positive sentiment at 87%, while negative sentiment accounted for only 13%, with the BSI KUR program being the primary driver of positive sentiment. These findings indicate that public perception of Islamic accounting in microfinance is highly positive, especially when compared to similar studies that tend to yield a more balanced distribution of sentiment between positive, negative, and neutral. In this context, the number of 9,546 mentions is significant, especially since it comes from a wide audience reach and involves thousands of online conversations across various information channels, which strengthens the social validity of these findings. From an academic perspective, this study contributes to the strengthening of Islamic accounting through an understanding of public perception and serves as a basis for regulators to promote transparency and consumer protection in Islamic microfinance. In conclusion, the use of sentiment analysis technology can provide real-time insights into public opinion and has the potential to become a strategic tool in enhancing public trust and participation in Islamic financial services.